2015
DOI: 10.1242/jcs.168351
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting IκBβ–NFκB signaling attenuates the expression of select pro-inflammatory genes

Abstract: Multiple mediators of septic shock are regulated by the transcription factor nuclear factor κB (NFκB). However, complete NFκB inhibition can exacerbate disease, necessitating evaluation of targeted strategies to attenuate the pro-inflammatory response. Here, we demonstrate that in murine macrophages, low-dose NFκB inhibitors specifically attenuates lipopolysaccharide (LPS)-induced IκBβ degradation and the expression of a select subset of target genes (encoding IL1β, IL6, IL12β). Gain-and loss-of-function exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
(80 reference statements)
2
26
0
Order By: Relevance
“…2A). Of note, Nfkbib encodes the NF-κB pathway inhibitor IκBβ (29). We next examined basal and lipopolysaccharide (LPS)-induced p65 nuclear translocation in primary WT and RKO microglia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). Of note, Nfkbib encodes the NF-κB pathway inhibitor IκBβ (29). We next examined basal and lipopolysaccharide (LPS)-induced p65 nuclear translocation in primary WT and RKO microglia.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Rev-erbα also binds to the Nfkbib promoter, but Rev-erbα deletion leads to decreased Nfkbib expression, suggesting that Rev-erbα binding may either act to somehow positively regulate Nfkbib transcription, or that the direct binding effects of Rev-erbα at the Nfkbib locus are minor and are counteracted by some indirect effect. Since Nfkbib acts as an inhibitor of NF-κB activation (29), loss of Nfkbib expression in Rev-erbα −/− cells could also promote inflammation. In macrophages, Rev-erbα/β integrate transcriptional signals from multiple damage-associated transcription factors, including NF-κB, Nrf2, and Smad3 (46), suggesting complex transcriptional regulation programs beyond canonical NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Each isoform uniquely contributes to the degree and duration of NFκB activation, as well as the NFκB transcriptome. Multiple studies have implicated IκBβ in TLR4‐mediated IL1β expression 78–80,90,91 . However, this is the first report linking IκBβ to IL1 expression following CpG‐ODN TLR9‐mediated innate immune signalling.…”
Section: Discussionmentioning
confidence: 79%
“…MAPKs also have an important role in inducing cytokine production. It has been previously established that inflammatory stimuli may lead to the activation of MAPK and the transcription factor NF-κB, which mediates the expression of several pro-inflammatory cytokines, including TNF-α, IL-1β, and IL-6 which have an important role in many inflammatory disease processes (34)(35)(36)(37). Previous studies indicated that p38 MAPK inhibitors can suppress IL-6 and TNF-α expression in monocytes and mast cells (38,39).…”
Section: Discussionmentioning
confidence: 99%